Understanding the information of shock effects between energy commodity prices and maritime freight rate - Chen, Feier; Tang, Juanjuan; Chen, Jianuo; Yin, Shuo; Du, Luhui; Fu, Guiyuan; Xu, Feng; Liang, Xiaofeng (Frontiers in Energy Research, 2024)
Research has identified volatility transmission from the oil market to the tanker freight market through external shocks. However, in the presence of intricate nonlinear structures, the academic literature often encounters difficulties in identifying cycles and their correlations across various timescales. This paper provides a multi-market analysis to comprehend the information from shock effects on different tanker routes and multi-peak fitting. Under different shock regimes, crude oil market and tanker freight rate shocks could transit bi-directly. When events occur, the crude oil market prices the expectations. However, when the actual performance of the future market differs from the traders’ predictions of the future market, a price gap exists. Generally, the trade opportunity is tough to catch up on because only partial information can be found. In this study, we investigate the volatility connection of multi-markets and shock effects to clarify previously undisclosed information using multi-peak analysis. The information gathered and double-checked by cargo markets, crude oil supply-demand balance, and tanker freight prices of various tanker types could assist us in identifying prospective trends and investment opportunities. The volatility of each market, as well as the correlation of multi-markets, gives insights to crude oil dealers, tanker market participants, and energy regulators.